Entropy Drives Calcium Carbonate Ion Association - Kellermeier, M.; Raiteri, Paolo; Berg, J.; Kempter, A.; Gale, Julian; Gebauer, D. (Wiley VCH, 2016)
The understanding of the molecular mechanisms underlying the early stages of crystallisation is still incomplete. In the case of calcium carbonate, experimental and computational evidence suggests that phase separation relies on so-called pre-nucleation clusters (PNCs). A thorough thermodynamic analysis of the enthalpic and entropic contributions to the overall free energy of PNC formation derived from three independent methods demonstrates that solute clustering is driven by entropy. This can be quantitatively rationalised by the release of water molecules from ion hydration layers, explaining why ion association is not limited to simple ion pairing. The key role of water release in this process suggests that PNC formation should be a common phenomenon in aqueous solutions.